The Impact of Ethical Leadership in The Effectiveness of Internal Auditing for Economic Units - Abidmuslim Hraiga, Raad; Wawi Jaas, Haitham; Hamza Marza, Ghaidaa (Iraqi Journal for Administrative Sciences, 2025)
The aim of the research is to review and explore the impact of ethical leadership on the effectiveness of internal auditing operations of economic units, as ethical leadership reflects positive traits such as honesty, integrity, trustworthiness, justice and altruism. Through these traits, a leader with good ethical behavior can influence his followers to enhance and develop ethical practices in the workplace, while the effectiveness of internal auditing is represented by its ability to achieve the goals for which it was created. The descriptive analytical approach was used to address the research questions, and it relied on a questionnaire distributed to a sample of (111) individuals from a community of (210) representing the field of application for employees of the Internal Audit Department and control units in the colleges of the University of Karbala, including academic instructors and graduate students. Then, the data were analyzed using the SPSS program to conduct reliability tests, formulate descriptive statistics, and analyze correlation and linear regression. The results showed a significant relationship and influence of ethical leadership on the effectiveness of internal auditing. The study concluded with important recommendations for strengthening ethical values ​​among members of internal audit departments. These departments should adopt policies based on the rules of professional conduct for auditing and internal auditing standards to increase the effectiveness of internal auditing and, consequently, raise the quality of its operations at the university level.